Joseph Priestley on metaphysics and politics: Jonathan Israel's 'Radical Enlightenment' reconsidered. Issue 1 (2nd January 2019) - Sakkas, Evangelos
ABSTRACT: This article probes Jonathan Israel's theory about 'Radical Enlightenment' inaugurating political modernity by way of explicating the thought of Joseph Priestley. In Israel's view, despite the inconsistencies plaguing Socinian thought, Priestley, a monist, emerged as an ardent supporter of religious toleration and democratic republicanism. This article seeks to restore the fundamental coherence of Priestley's theological and metaphysical views, arguing that they were produced as parts of a system founded on the simultaneous adherence to providentialism and necessitarianism. Prized as a prerequisite of the unfolding of the divine plan, the unobstructed expression of religious opinions was the centre of the conception of civil society and civil liberty that Priestley articulated based on these premises and his forays into politics aimed to secure its permanence. A comparison of Priestley's stance on the issue of manhood suffrage with that of Richard Price reveals not the materialist Priestley, but Price, a dualist, as an advocate of democratization and casts into doubt the applicability of Israel's scheme in the case of England. The article closes with some suggestions towards reappraising the relationship between Enlightenment and modernity.